2022
DOI: 10.1177/22808000221101809
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of N-glycosylated chitosan/polyvinyl alcohol hydrogels for use in wound dressings

Abstract: Chitosan and its derivatives show potent biocompatibility, biodegradability, antimicrobial activity, hemostatic effects, and wound healing properties. Their application in wound dressings has garnered substantial research interest. In this work, we prepared a drug-loaded hydrogel by mixing N-glycosylated chitosan with polyvinyl alcohol (PVA), followed by loading of ofloxacin. A 2:1 volume ratio of chitosan to PVA was found to be optimal based on swelling and water evaporation rates. The slow-drug-release perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Yi et al mixed N-glycosylated chitosan and polyvinyl alcohol and loaded ofloxacin to prepare a series of multifunctional hydrogel dressings. In their in vivo wound model experiments, the hydrogel presented good antibacterial activity and great potential for promoting wound healing [ 105 ].…”
Section: Chitosan-based Hydrogel Dressingsmentioning
confidence: 99%
“…Yi et al mixed N-glycosylated chitosan and polyvinyl alcohol and loaded ofloxacin to prepare a series of multifunctional hydrogel dressings. In their in vivo wound model experiments, the hydrogel presented good antibacterial activity and great potential for promoting wound healing [ 105 ].…”
Section: Chitosan-based Hydrogel Dressingsmentioning
confidence: 99%
“…Chitosan (CS) is a product of deacetylation of chitin, containing free amino groups that are modified to exhibit excellent biological functionality. Meanwhile, chitosan has good inhibitory effects on both Escherichia coli and Staphylococcus aureus, making it widely used in the field of biomedical research [11][12] . Sodium alginate (SA) is one of the most common byproducts of biomass, and it has good biological safety.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, investigations on wound dressings have suggested that hydrogel could provide a humid microenvironment, stimulate endogenous cell proliferation, maintain gaseous exchange necessary for tissue breathing, and repair epidermal or dermal injury. 1 Bioactive substances, macromolecules, and biocompatible materials, especially natural polymers derived from plants, have been evaluated as primary materials or ingredients in producing hydrogels used in wound healing. 2 Bletilla striata polysaccharide (BSP) (MW = 65-260 kDa) is a natural glucomannan with numerous hydroxyl groups derived from B. striata, a traditional Chinese herb widely utilized in the treatment of mucosal damage, bleeding, burns, and recovery enhancement for many years.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, investigations on wound dressings have suggested that hydrogel could provide a humid microenvironment, stimulate endogenous cell proliferation, maintain gaseous exchange necessary for tissue breathing, and repair epidermal or dermal injury. 1 Bioactive substances, macromolecules, and biocompatible materials, especially natural polymers derived from plants, have been evaluated as primary materials or ingredients in producing hydrogels used in wound healing. 2…”
Section: Introductionmentioning
confidence: 99%